Вы находитесь на странице: 1из 5

.



1
f (x) = sin x2 x = 0:

P
(1)n 2n+1
sin t =
t
t = x2 .
(2n+1)!
n=0

. :
? ..
?

I.

( )
f (g(x)), 2 :
f (t) = f (0) +

f 0 (0)
f 00 (0) 2 f (3) (0) 3
t+
t +
t + ...
1!
2!
3!

t = g(x) = g(0) +

g 0 (0)
g 00 (0) 2 g (3) (0) 3
x+
x +
x + ...
1!
2!
3!

g(0) = 0.
Th
f (g(x)) , ..


g 00 (0) 2 g (3) (0) 3
g 0 (0)
x+
x +
x + ... +
g(0) +
1!
2!
3!

2
f 00 (0)
g 0 (0)
g 00 (0) 2 g (3) (0) 3
+
g(0) +
x+
x +
x + ... +
2!
1!
2!
3!

3
f (3) (0)
g 0 (0)
g 00 (0) 2 g (3) (0) 3
+
g(0) +
x+
x +
x + ... + ...
3!
1!
2!
3!
f (g(0))0
f (g(0))00 2 f (g(0))(3) 3
f (g(0)) +
x+
x +
x + . . . (1)
1!
2!
3!

f 0 (0)
f (g(x)) = f (0) +
1!

:

n X

X
f (n) (0)
g 0 (0)
g 00 (0) 2 g (3) (0) 3
f (g(0))(n) n
g(0) +
x+
x +
x + ...
x
n!
1!
2!
3!
n!
n=0
n=0

(2)

, ,
. , ,
,
1
2

a.s.savostyanov@gmail.com
:

1) ,
;
2) x0 = 0 . x0 .

xn
. :

n X

X
f (n) (0)
g 0 (0)
g 00 (0) 2 g (3) (0) 3
g(0) +
x+
x +
x + ... =
an x n ,
n!
1!
2!
3!
n=0
n=0

(3)

an R
. , ..:
f (g(0))(n)
an =
(4)
n!

II.

n = 0, 1, 2. :
f (g(x))(0) = f (g(x))
(5)
f (g(x))(1) = f 0 (g(x))g 0 (x)
0

(6)

f (g(x))(2) = (f 0 (g(x))g 0 (x)) = f (2) (g(x))g 0 (x)2 + f 0 (g(x))g (2) (x)

(7)

f (g(x))(3) = f (3) (g(x))g 0 (x)3 + 3f (2) (g(x))g 0 (x)g (2) (x) + f 0 (g(x))g (3) (x)

(8)

, - n. , 4-
:
f (g(x))(4) = f (4) (g(x))g 0 (x)4 + 6f (3) (g(x))g (2) (x)g 0 (x)2 + 4f (2) (g(x))g (3) (x)g 0 (x)+
+ 3f (2) (g(0))g (2) (x)2 + f 0 (g(x))g (4) (x) (9)

.
n,
:
.
1. an , n
.
I
, , g(0) = 0 , :
k  0
k

g 00 (0) 2 g (3) (0) 3
g (0)
g 00 (0) 2 g (3) (0) 3
g 0 (0)
x+
x +
x + ... =
x+
x +
x + ... =
g(0) +
1!
2!
3!
1!
2!
3!
 0
k
g (0) g 00 (0)
g (3) (0) 2
k
=x
+
x+
x + ...
(10)
1!
2!
3!
, k. , xn n .

, .
:
1) n = 0.
n = 0 f (g(x))(0) = f (g(0)). , .. g(0) = 0 x0
f (0) = f (g(0)).
2

2) n = 1.
. ,
, x ,
, , f 0 (g(0))g 0 (0). ,
.
3) n = 2.
00

x2 1- 2- : f 0 (g(0)) g 2!(0) ,
00
: f (g(0))
g 0 (0)2 ( , 2!
, ).
f (g(0))(2) . , , .
n = 3 .., .
.

III.

, , , ,
, ..
n xn , n! ( 4). n
.
.
2. n f (g(x)) ( ) :
(n)

f (g(x))

n
X

(k)


(g(x)) Bn,k

k=0

Bn,k
:

g (1) (x) g (2) (x)


g (nk+1) (x)
,
,
.
.
.
1!
2!
(nk+1)!

g (1) (x) g (2) (x)


g (nk+1) (x)
,
,...
1!
2!
(n k + 1)!


,

(11)

Bn,k (x1 , x2 , . . . xnk+1 ) =



mnk+1
 x m 1  x m 2
X
xnk+1
n!
1
2

...

, (12)
=
m1 !m2 ! . . . mnk+1 !
1!
2!
(n k + 1)!
mi ,
1. m1 + m2 + . . . + mnk+1 = k;
2. 1m1 + 2m2 + . . . + (n k + 1)mnk+1 = n;

,
. ,
-- 1855 3 .
3
, , .
1800- .

. 1:
.
3. n n.
I
1 .
n f (n) (g(x)),
, xn

k
g 00 (0) 2 g (3) (0) 3
n! g 0 (0)
x+
x +
x + ...
k!
1!
2!
3!
 (1)

(2)
(nk+1) (x)
Bn,k g 1!(x) , g 2!(x) , . . . g (nk+1)!
. ( : n! 4, k!
).
, k
k , ,
k , i . ,
- n k + 1,
n. ,
nk +2, k 1 x
1, n.
n k + 1.
00
0
m1 g 1!(0) x, m2 g 2!(0) x2 ,
. . . , mnk+1

g (nk+1) (0) nk+1


x
,
(nk+1)!

mi .
nk+1
P
,
mi = k, ,
i=1

xn ,

nk+1
P

mi i = n,

i=1

i xi .
, ,
, {mi }. ,
k m1 , m2 , . . .,
, , :
k!
m1 ! m2 ! . . . mnk+1 !


, , ,
, .

IV.

, .
, , ,
.
, , , .. --, .
, ,
, --

, (, ). ,
4 , .
,
, ,
. ,
, --
, .

4
, (Louis Comtet) Advanced Combinatorics,
, , , (Steven Roman)
Formula of Faa Di Bruno, .